Efficacy of Platinum Rechallenge in Metastatic Urothelial Carcinoma After Previous Platinum-Based Chemotherapy for Metastatic Disease. (17th August 2021) - Wong, Risa L.; Ferris, Lorin A.; Do, Olivia A.; Holt, Sarah K.; Ramos, Jorge D.; Crabb, Simon J.; Sternberg, Cora N.; Bellmunt, Joaquim; Ladoire, Sylvain; De Giorgi, Ugo; Harshman, Lauren C.; Vaishampayan, Ulka N.; et al.
Abstract : Background: Fit patients with metastatic urothelial carcinoma (mUC) receive first-line platinum-based combination chemotherapy (fPBC) as standard of care and may receive additional later-line chemotherapy after progression. Our study compares outcomes with subsequent platinum-based chemotherapy (sPBC) versus subsequent non-platinum-based chemotherapy (sNPBC). Materials and Methods: Patients from 27 international centers in the Retrospective International Study of Cancers of the Urothelium (RISC) who received fPBC for mUC and at least two cycles of subsequent chemotherapy were included in this study. A multivariable Cox proportional hazards model compared overall survival (OS) and progression-free survival (PFS). Results: One hundred thirty-five patients received sPBC and 161 received sNPBC. Baseline characteristics were similar between groups, except patients who received sPBC had higher baseline hemoglobin, higher disease control rate with fPBC, and longer time since fPBC. OS was superior in the sPBC group (median 7.9 vs 5.5 months) in a model adjusting for comorbidity burden, performance status, liver metastases, number of fPBC cycles received, best response to fPBC, and time since fPBC (hazard ratio, 0.72; 95% confidence interval, 0.53–0.98; p = .035). There was no difference in PFS. More patients in the sPBC group achieved disease control than in the sNPBC group (57.4% vs 44.8%; p = .041). Factors associated with achieving disease control in the sPBC group but not the sNPBC group included longer time since fPBC, achieving disease control with fPBC, and absence of liver metastases. Conclusion: After receiving fPBC for mUC, patients who received sPBC had better OS and disease control. This may help inform the choice of subsequent chemotherapy in patients with mUC. Implications for Practice: Patients with progressive metastatic urothelial carcinoma after first-line platinum-based combination chemotherapy may now receive immuno-oncology agents, erdafitinib, enfortumab vedotin, or sacituzumab govitecan-hziy; however, those ineligible for these later-line therapies or who progress after receiving them may be considered for subsequent chemotherapy. In this retrospective study of 296 patients, survival outcomes and disease control rates were better in those receiving subsequent platinum-based rechallenge compared with non–platinum-based chemotherapy, suggesting that patients should receive platinum rechallenge if clinically able. Disease control with platinum rechallenge was more likely with prior first-line platinum having achieved disease control, longer time since first-line platinum, and absence of liver metastases. Abstract : This article examines differences in outcomes for patients treated with platinum-based combination chemotherapy for metastatic urothelial carcinoma who later received subsequent platinum-based chemotherapy or subsequent non-platinum-based chemotherapy. Clinical factors associated with better outcomes are reported.